Pengaruh Ukuran Perusahaan, Audit Internal, Opini Audit, Ukuran KAP, Terhadap Audit Delay Pada Perusahaan Sektor Batu Bara - Sugiyanti, Dedek; Sekarsari, Wida Dwi; Septilia, Nike Gadis; Susilo, Dwi Ermayanti (Universitas Dian Nuswantoro, 2023)
This study aims to determine the effect of company size, internal audit, audit opinion, KAP size, on audit delay in coal sector companies listed on the Indonesia Stock Exchange (IDX). This research uses a descriptive type with a comparative causal approach, which is measured using the classic assumption test method, a method based on multiple linear regression and hypothesis testing with SPSS 26. The population in this study is 20 companies and the period used is 2019 to 2021. The sample determined based on purposive sampling method with a total sample of 60 Financial Statements. The results of the study prove that company size has a significant and negative effect on audit delay, internal audit has no significant effect on audit delay, audit opinion has a positive and significant effect on audit delay, KAP size has no significant effect on audit delay.